Peripheral Ulcerative Keratitis : A Comprehensive Guide - Tandon, Radhika; Galor, Anat; Sangwan, Virender Singh; Ray, Manotosh (Springer International Publishing : Imprint: Springer, 2017)
A handy manual for cornea specialists, this book provides detailed practical information about a complex, sight-threatening disease that can be challenging to diagnose and manage. This text features chapters dedicated to outlining all facets of diagnosis and management while covering both medical and surgical treatment options. Peripheral Ulcerative Keratitis, supplemented with useful references and appendices to provide simple step by step algorithms, is written by internationally renowned authors who are experts in the field. Including practical tips and guidelines for diagnosis and therapy of these disorders, Peripheral Ulcerative Keratitis is designed to serve as a guide for comprehensive ophthalmologists and should find itself on the bookshelves of ophthalmology clinics, corneal practices and training programs across the country. .
Keywords: Medicine.; Ophthalmology.; elektronické knihy; electronic books